INTERNAL TOURISM DEVELOPMENT STRATEGY INCREASING REGIONAL ORIGINAL INCOME (PAD) IN JAYAPURA CITY PAPUA PROVINCE - Fredrick Hendrick Mebri; Ermaya Suradinata; Kusworo Kusworo (Jurnal Ilmiah Wahana Bhakti Praja, 2022)
ABSTRACT. Regional Original Income (PAD) is an illustration of regional financial potential, where there are various sectors that can be developed to increase regional original income, one of which is the tourism sector, so that the existence of tourism is expected to be a contributor to regional original income, but the tourism sector in Jayapura City have not been managed and utilized optimally, in fact many tourism assets in Jayapura City are still controlled by customary rights owners by conducting illegal levies, lack of cooperative relationships with related agencies in building and developing tourist objects, and lack of community participation in developing tourist objects. Based on this, the authors are interested in conducting research with the title; "Tourism Development Strategy in Increasing Regional Original Income (PAD) in Jayapura City, Papua Province. This study uses a qualitative method with a descriptive approach to describe the situation in the field which is then investigated to find solutions to general problems. The data collected for this study is data related to ASOCA's analysis of tourism development strategies in increasing local revenue (PAD) and its implications in determining the strategy to be carried out by the Jayapura City Tourism Office, Papua Province. This study was made to find out and explain the extent to which the Tourism Office's strategy in tourism development to increase local revenue in Jayapura City is in line with the phenomena that describe the obstacles faced and efforts to overcome obstacles. Key words: Strategy, Regional Original Income (Pad), Tourism.